Efficacy and Tolerability of STOPAIN for a Migraine Attack - St. Cyr, Andrea; Chen, Ashley; Bradley, Kathleen C.; Yuan, Hsiangkuo; Silberstein, Stephen D.; Young, William B. (Frontiers in Neurology, 2015)
Objective To determine whether topical menthol 6% gel will relieve a migraine attack. Materials and Methods A single-center, open-label pilot trial of 25 patients with at least one year of diagnosed episodic migraine and < 15 headache days per month. Patients treated one migraine attack with STOPAIN topical menthol 6% gel to skull base within 2 hours of headache onset. Headache pain severity was assessed prior to and after gel application. Results Thirty-two patients enrolled and 25 completed the study. Prior to treatment, seven patients had mild pain, 13 moderate pain, and five severe pain. Two hours following gel application, 7 patients had no pain, 7 mild pain, 6 moderate pain and 5 severe pain. The majority of patients had similar pain intensity (8; 32 %) or improvement (13; 52%). At 24-hour, only 2 non-rescued patients still had mild headache. Of the 25 completers, two patients took rescue medication prior to the 2-hour period, and an additional 10 patients rescued between 2 and 24 hours. Conclusion Study results showed a significant improvement in headache intensity by 2 hours after gel application. This pilot study shows STOPAIN gel may be effective in treating an acute migraine attack.